Film adaptation of the post-apartheid South African novel: re-examining the aesthetics of creation of disgrace - Sawadogo, Denis (Department of English Language and Literature, 2023)
While many scholarships of the film adaptation of Disgrace have championed the fidelity rhetoric of the film with respect to J.M. Coetzee's novel, and in so doing, have advocated the axiomatic hierarchy of literature over cinema, this dissertation challenges the fidelity discourse about the film and proposes new tropes for adaptation criticism beyond the classical paradigm. Central to the thesis is the argument that a re-examination of Steve Jacobs's feature film Disgrace unveils the inconsistency and inadequacy of the fidelity rhetoric as a language for adaptation criticism, positions the film as an independent genre with its specificity and poeticity, and allows for an intertextual dialogue with other post-apartheid South African and postcolonial African cinematic productions as a means of promoting adaptation criticism beyond the fidelity model. While cementing the film's independent status vis-à-vis the novel, the intertextual critique also allows for a rewriting of Jacobs's Disgrace that addresses its shortcomings and controversies. Hence, drawing upon structural narratologists such as Gerard Genette, postcolonial scholars such as Gayatri Spivak and Frantz Fanon, and adaptation critics including Linda Hutcheon, Robert Stam, Alexie Tcheuyap, and Lindiwe Dovey, the dissertation explores at a time formal and thematic aesthetics of the film adaptation to diversify its critical avenues not only but also to bridge epistemological gaps left by previous studies which are limited to thematic hermeneutics.